Management of refractory cervical anastomotic fistula after esophagectomy using the pectoralis major myocutaneous flap - Deng,Lifei (2022)
Abstract Introduction A refractory cervical anastomotic fistula which postoperatively remains unhealed for more than 2 months under conservative care severely impacts the quality of life of the patient and potentially leads to anastomotic stricture after the fistula heals. It is widely accepted that, to avoid this complication, refractory cervical anastomotic fistulas should undergo more aggressive treatments. However, when and which surgical intervention should be considered is unclear. Objective This study was designed to evaluate the role of the pectoralis major myocutaneous flap in the management of refractory cervical anastomotic fistulas based on our experience of 6 cases and a literature review. Methods Six patients diagnosed with refractory cervical anastomotic fistula after esophagectomy treated using pectoralis major myocutaneous flap transfer were included in the study. The clinical data, surgical details, and treatment outcome were retrospectively analyzed. Results All patients survived the operations. One patient who had a circumferential anastomotic defect resulting from surgical exploration developed a mild fistula in the neo-anastomotic site in the 5th postoperative day, which healed after 7 days of conservative care. This patient developed an anastomotic stricture which was partially alleviated by an endoscopic anastomotic dilatation. All the other 5 patients had uneventful recoveries after operations and restored oral intake on the 10th-15th days after operation, and they tolerated normal diets without subsequent sequelae on follow-up. One patient developed both local and lung recurrence and died in 15 months after operation, while the other 5 patients survived with good tumor control during the follow-up of 25-53 months. Conclusion The satisfactory treatment outcome in our study demonstrates that pectoralis major myocutaneous flap reconstruction is a reliable management modality for refractory cervical anastomotic fistulas after esophagectomy, particularly for those patients who experienced persistent fistulas after conservative wound care and repeated wound closures.